Teachers’ Motivational Support, Academic Self-Efficacy and Academic Motivation : The SEM investigation of Naval Cadets’ Engagement - Nurnindyah, Dewi; Pramadi, Andrian; Pandjaitan, Lena (Universitas Ahmad Dahlan, 2023)
The success of the development of Navy Soldiers in terms of Tanggap, Tanggon, and Trengginas within the context of military education is influenced by the naval cadets’ engagement during the learning process. This study aimed to test the conceptual model of the engagement of naval cadets in learning in terms of teachers’ motivational support, academic self-efficacy, and academic motivation. The data was obtained from 514 naval cadets and analyzed with SEM using the AMOS program. The scale of the University Student Engagement Inventory (USEI), Patterns Adaptive Learning Strategies (PALS), Motivated Strategies Learning Questionnaire (MSLQ), and Teacher as Social Context Questionnaire (TASCQ) were utilized. The results showed that teachers’ motivational support as social facilitators had a significant role in increasing the naval cadets’ engagement in the context of military education through personal facilitators, namely academic self-efficacy and mastery goal orientation. Meanwhile, performance goal orientation did not have a significant contribution as a mediator. This study provided input to naval cadets, lecturers/educators, and military educational institutions to emphasize the importance of the role of teachers' support, academic self-efficacy, and academic motivation